1979
DOI: 10.1530/jrf.0.0550125
|View full text |Cite
|
Sign up to set email alerts
|

Varying effects of an IUD on decidualization in mice

Abstract: Chronically implanted IUDs consisting of silk suture threads induced decidualization in regions of the uterus remote from the suture site in ovariectomized mice treated with a regimen of progesterone and oestrogen which sensitizes the uterus to a decidual stimulus. In these conditions the IUDs did not inhibit decidualization induced by instilled oil, although they did so in pregnant animals of the same strain. Varying the dose of progesterone and oestrogen did not produce conditions in which IUD's inhibited oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

1979
1979
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…4). Although Martin & Finn (1979) observed that the oil had disappeared from most IUD-bearing uteri 44 h after injection, in the present study it was still evident at 6 h. The complete failure of this oil to induce a vascular reaction suggests that the IUD-bearing uterus shows a general insensitivity to potential deciduogenic stimuli. This would also be consistent with the fact that there was little increase in uterine vascular permeability even in the region of the IUD thread itself.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…4). Although Martin & Finn (1979) observed that the oil had disappeared from most IUD-bearing uteri 44 h after injection, in the present study it was still evident at 6 h. The complete failure of this oil to induce a vascular reaction suggests that the IUD-bearing uterus shows a general insensitivity to potential deciduogenic stimuli. This would also be consistent with the fact that there was little increase in uterine vascular permeability even in the region of the IUD thread itself.…”
Section: Discussioncontrasting
confidence: 76%
“…The degree of continuity between the lumina of the two uterine horns of mice seems to undergo subtle changes: in contrast to the findings in ovariectomized females, instilled materials rarely cross to the contralateral horn after oestradiol and progesterone treatment (Martin & Finn, 1979; unpublished observation). The relative independence of the two horns after progesterone plus oestradiol treatment is reflected by the generally isolated response of the instilled horn.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Randomly bred female Swiss Schneider mice were housed, allowed to become pregnant, or ovariectomized as described by Martin & Finn (1979 10:30-11:30 h on Day 5. At 15 min before death they were anaesthetized with tribromoethanol and given 0-2 ml of 2% Pontamine Blue i.v.…”
Section: Methodsmentioning
confidence: 99%